Governing social inclusion Europeanization through policy coordination - Armstrong, Kenneth A. (Oxford : Oxford University Press, 2010)
The Treaty of Amsterdam committed EU member states to tackle social exclusion. This book aims to explore, from an inter-disciplinary perspective, the possibilities and limitations of the attempts by the EU to co-ordinate and 'Europeanize' member states' strategies and policies.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social integration -- European Union countries; European Union countries -- Social policy